WEB-BASED LEARNING MEDIA APPLICATION - M. Arinal Ihsan; Teuku Rinal Liza; Darma setiawan; Asmaidi Asmaidi (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2019)
The learning model currently applied at the South Aceh Polytechnic is conventional. Students only listen to the lecturers’ presentation and thus they easily get bored, tired and declining learning motivation. This due to the lack of transfer knowledge experienced by students, resulted in students being unable to grasp the material presented by lecturers whilst some students assigned lower achiever. This study aims to develop a web-based learning media application at the South Aceh Polytechnic. Web-based learning media developed with MySQL and PHP programming languages. The research method used is the waterfall research method combined with observation and interviews. The collected data is then analyzed descriptively. The results of this study that delivering lesson through website-based learning media can improve students' performance in a typical courses.